The Impact Distribution of Zakat in Alleviating Poverty During COVID-19 Pandemic: Evidence From Indonesia - Arbi, Dion Saputra; Satyadharma, Jonathan Farez; Hidayat, Ihsan (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2024)
Zakat is one of the Islamic socio-economic instruments to improve the welfare of Muslim communities by reducing poverty levels. Between 2020-2022, when the COVID-19 pandemic hit Indonesia, zakat management institutions succeeded in getting 1,145,636 people out of poverty, thereby increasing the achievements of mustahik to muzakki by augmenting individual and household sources of income from zakat recipients. This study uses the CIBEST analysis tool and the BAZNAS Welfare Index (IKB) to measure the impact of zakat distribution by BAZNAS on poverty alleviation during the COVID-19 pandemic in Indonesia. The results of this study indicate that zakat distribution can alleviate the poverty of the Indonesian population by 4.14 percent during the COVID-19 pandemic.Thus, the distribution of zakat funds during the pandemic era significantly reduced Indonesia’s poverty. Abstrak:Zakat merupakan salah satu instrumen sosial-ekonomi Islam yang  meningkatkan kesejahteraan masyarakat Muslim dengan menurunkan tingkat  kemiskinan. Sepanjang tahun 2020-2022, pada masa pandemi COVID-19  melanda Indonesia, Badan Zakat Nasional (BAZNAS) sukses mengentaskan  sebanyak 1.145.636 orang keluar dari kemiskinan sehingga meningkatkan pencapaian  kemampuan dari mustahik menjadi muzaki dengan menambah sumber pendapatan  individu dan rumah tangga dari penerima zakat. Penelitian ini menggunakan  analisis alat CIBEST dan Indeks Kesejahteraan BAZNAS (IKB) untuk mengukur  dampak dari pendistribusian zakat oleh BAZNAS dalam mengentaskan kemiskinan  sepanjang pandemi COVID-19 di Indonesia. Hasil penelitian ini menunjukkan  penyaluran zakat dapat menurunkan tingkat kemiskinan Indonesia sebesar 4,14  persen sepanjang pandemi COVID-19. Dengan demikian, pendistribusian dana zakat  pada masa pandemi COVID-19 secara signifikan mampu mengurangi tingkat  kemiskinan di Indonesia.